Instrument Validity and Reliability Confidence to Jump serve in Volleyball - Arif Purnomo Arif; Sujarwo Sujarwo (STKIP Muhammadiyah Kuningan, 2022)
This research is based on the validity and reliability of the confidence instrument against jump serve. The purpose of this study was to determine the level of validity and reliability of the confidence instrument against jump serve. The research method uses descriptive quantitative research. The instrument in this study was a questionnaire about athletes' self-confidence with a total of 68 statements about the confidence factor, namely: 1) optimistic; 2) independent; 3) likes the sport they do; 4) have no worries; 5) can adapt. The subjects of this study were 12 extracurricular volleyball athletes at SMA Negeri 1 Bambanglipuro, Bantul. Content validity using the Delpi technique with two experts in sports psychology and volleyball and reliability using Cronbach's Alfa. The results of the instrument validation to measure the volleyball athlete's confidence in performing the jump serve were validated in content and empirically the instrument to measure the volleyball athlete's confidence in performing the jump serve. The content validity of the Delphi results from the two experts obtained agreement and correction that this instrument needed to be improved in preparing negative statement instructions and technically when to fill out the questionnaire. Using the Pearson Product Moment, empirical validity obtained the results of the trials carried out; from the 68 initial questions, 12 items fell out. So that the remaining 56 questions are valid. The instrument's reliability with empirical calculations shows that this instrument has high reliability, namely: 0.979. Based on the validity and reliability test of the instrument, this instrument is suitable to be used to measure the confidence of volleyball athletes in performing jump services.